Balancing International Recognition and Domestic Pressure: A Two-Level Games Analysis of Indonesia's Board of Peace (BOP) Policy 2026 - Moh. Arief Rakhman; Muliono; Marlita Andhika Rahman (Mandala: Jurnal Ilmu Hubungan Internasional, 2026)
This article analyzes the conditions under which Indonesia's two negotiating tables became irreconcilable in the Board of Peace (BoP) episode of 2026 and what this incompatibility reveals about the structural limits of Indonesia's foreign policy under President Prabowo. Using Putnam's two-level games framework (1988), updated for the digital age by Bjola and Manor (2018), this study maps how two simultaneous win-sets the international level (L1), where BoP offered Indonesia recognition as a global peacemaker, and the domestic level (L2), where Indonesia's Muslim-majority public, mobilized by MUI fatwas and deep-rooted anti-normalization sentiment, created a win-set fundamentally incompatible with any arrangement perceived as supporting Israel were managed, negotiated, and ultimately could not be satisfied simultaneously. The article argues that Indonesia's choice to contribute troops rather than pay the USD 1 billion membership fee was a rational two-level negotiation solution to keep both win-sets viable. However, the U.S.-Israel attack on Iran on February 28, 2026 rendered both win-sets irreconcilable overnight, making suspension the only remaining rational move. The case further exposes a structural weakness: a personalized foreign policy architecture without adequate institutional vetting mechanisms, which produced contradictions between presidential and ministerial statements and accelerated the incompatibility of the two tables. This article provides the first systematic two-level games analysis of the BoP episode in Indonesian foreign policy scholarship.